Nutritional Values of Artocarpus odoratissimus (Terap) Fruit and its Antioxidant Capacity as Affected by Superheated-steam Treatment - Othman, Azizah; Hassan, Nurul Nadia; Jahan, Shahrina Shah; Husen, Rafidah (Jurnal Gizi dan Pangan, 2024)
This study was carried out to evaluate the nutrient composition, Total Phenolic Content (TPC), Total Flavonoid Content (TFC) and antioxidant capacity of Artocarpus odoratissimus by using DPPH and FRAP assays. Results showed that nutrient compositions were quite similar to other reported studies. As for the antioxidant potential of the fruit, both the flesh and seed treated with Superheated-Steam (SHS) showed significantly higher TPC, TFC, 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and Ferric Reducing Antioxidant Power (FRAP) (except the flesh showing no significant difference) values compared to the Freeze-Dried (FD) samples. The SHS-treated seed showed the highest values in all the assays conducted, exhibiting the superior antioxidant potential of the seed over the flesh. The seed also contained a higher composition of fat, protein, ash and carbohydrate than the flesh, while the flesh, on the other hand, showed higher moisture content and crude fibre compared to the seed (p<0.05). This study has demonstrated that SHS has the ability to enhance the polyphenolic compounds and antioxidant capacity of terap fruit.